A Comparative study of microleakage in bioactive composite resin restoration with filled and unfilled bonding materials - Maulana, Afrizal; Widyastuti, Noor Hafida; Faizah, Ariyani; Ningsih, Juwita Raditya (Majalah Kedokteran Gigi Indonesia, 2024)
The most recent development in composite resin is bioactive resin, which replaces common resin. If ignored, the tendency for shrinking in bioactive composite resin could result in microleakage. Bonding material innovations that incorporate more filler have also been created to reduce this issue and lower the possibility of microleakage. The purpose of this study is to compare the microleakage of bioactive composite resin restorations with and without filled bonding material. Thirty-two maxillary first premolar samples were split into two groups: group A containing 16 samples repaired with unfilled OptiBondTM Universal (Kerr) and group B containing 16 samples restored with filled SingleBond Universal (3 M). Utilizing ACTIVATM BioACTIVE-Restorative (Pulpdent), the samples from both groups were restored.The specimens were subjected to a 24-hour artificial saliva incubation period, succeeded by an equivalent duration of exposure to 2% methylene blue. A USB digital microscope stereo was used to measure the microleakage by observing the methylene blue 2% penetration depth. Microleakage was 8.95% in group A and 8.83% in group B, according to the results. The findings of the the parametric test using the independent t-test showed that there was no significant difference (p > 0.05) in microleakage across the bioactive composite resin restoration groups. This indicates that the microlekeage of bioactive composite resin restoration is unaffected by the presence of filler in the bonding agent.